Urban Tourism in Bali From a Public Administration Perspective - I Wayan Budiartawan; Nyoman Diah Utari Dewi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
The development of urban tourism in Bali has become increasingly complex alongside the growth of tourism activities, rising pressure on public services, and mounting demands for social and environmental sustainability. This condition underscores the urgency of studies that view tourism not merely as an economic sector, but also as an arena of public administration and governance. This study aims to analyze the relationship between urban tourism and public administration practices, as well as to identify relevant policy implications within Bali’s urban context. The theoretical framework draws on the concepts of urban tourism, destination governance, and public administration, with particular attention to institutional capacity and cross-sectoral coordination. The research employs a qualitative method using a literature review approach, drawing on academic books, scholarly journal articles, and policy documents. The findings indicate that the effective management of urban tourism is strongly influenced by local government institutional capacity, clarity of roles among stakeholders, and the integration of cross-sectoral policies. These results highlight the importance of strengthening public governance as a prerequisite for the sustainability of urban tourism. Keywords: Destination Governance, Public Administration, Urban Tourism.